Evaluating The Effectiveness of Islamic Family Law Reform and Public Legal Awareness in Preventing Underage Marriage in Tegal: A Study after the Enactment of Law No. 16 of 2019 - Ali, Nur; Meidina, Ahmad Rezy; Imam Sibawaih (KALOSARA: Family Law Review, 2026)
The study examines the effectiveness of Islamic family law reform and the level of public legal awareness regarding underage marriage following the enactment of Law Number 16 of 2019 in Tegal Regency and Tegal City. While the amendment, which raised the minimum legal age of marriage to nineteen for both men and women, represents a significant normative shift, the persistence of underage marriage indicates a gap between legal reform and its social implementation. This study addresses the gap by analyzing how legal awareness and socio-cultural factors influence the effectiveness of the reform at the community and institutional levels. Employing a socio-legal approach, this research integrates normative legal analysis with empirical fieldwork involving interviews, observations, and document analysis conducted with religious court officials, marriage registrars, community leaders, and affected families across selected districts in Tegal. The findings demonstrate that although the legal framework has strengthened institutional control over marriage registration, its effectiveness remains uneven due to varying levels of legal awareness, entrenched socio-cultural norms, economic pressures, and the strategic use of marriage dispensation mechanisms. The study concludes that legal reform alone is insufficient to reduce underage marriage without complementary efforts to enhance legal literacy and address structural social factors. This research recommends strengthening institutional coordination, improving community-based legal education, and reforming the dispensation mechanism to ensure stricter and more consistent application. By linking legal reform with legal consciousness and social practice, this study contributes to the discourse on the effectiveness of Islamic family law in plural and dynamic societies, while offering policy-relevant insights for improving family law governance in Indonesia.   Keywords: islamic family law reform; legal awareness; socio-legal studies; underage marriage.